SWI/SNF Complex Genomic Alterations as a Predictive Biomarker for Response to Immune Checkpoint Inhibitors in Multiple Cancers - Di Wang; Jianchao Wang; Dongmei Zhou; Zhixian Wu; Wei Liu; Yanping Chen; Gang Chen; Jing Zhang (2023)
Whether there is an association between SWI/SNF genomic alterations in tumors and response to immune checkpoint inhibitors (ICI) remains unclear because prior studies have focused on either an individual gene or a predefined set of genes. Herein, using mutational and clinical data from 832 ICI-treated patients who underwent whole-exome sequencing, including sequencing of all 31 genes of the SWI/SNF complex, we found that SWI/SNF complex alterations were associated with significantly improved overall survival (OS) in melanoma, clear-cell renal cell carcinoma, and gastrointestinal cancer, as well as improved progression-free survival (PFS) in non-small cell lung cancer. Including tumor mutational burden as a variable, the multivariate Cox regression analysis showed SWI/SNF genomic alterations had prognostic value in melanoma [HR, 0.63 (95% confidence interval, CI, 0.47-0.85), P = 0.003], clear-cell renal cell carcinoma [HR, 0.62 (95% CI, 0.46-0.85), P = 0.003], and gastrointestinal cancer [HR, 0.42 (95% CI, 0.18-1.01), P = 0.053]. Furthermore, we used the random forest method for variable screening, identifying 14 genes as a SWI/SNF signature for potential clinical application. Significant correlations were observed between SWI/SNF signature alterations and improved OS and PFS in all cohorts. This suggests that SWI/SNF gene alterations are associated with better clinical outcomes in ICI-treated patients and may serve as a predictive marker for ICI therapy in multiple cancers.